Teacher perspectives on collaboration between English foreign language and special education teachers in Finnish primary schools - Horelli, Iida (2019)
In this study, four English as a foreign language (EFL) and two special education (SPED) teachers’ perspectives on their collaboration and the three-step support model as a part of foreign language education were gathered through individual interviews and analysed in qualitative methods. The focus of the study was on (1) these teachers’ collaboration practices; (2) the enablers and barriers of their collaboration; (3) the benefits and limitations of the three-step support model in the context of EFL. The aim of this study was to share individual teachers’ experiences of the collaboration between SPED and EFL teachers and to possibly evoke discussion on the current state and possible areas for development in the collaboration and EFL support in Finnish primary school education. The teachers’ attitudes towards teacher collaboration appeared positive, yet there was infrequency in their practical implementations of collaboration. The most common collaboration method among the participants was consultation. In co-teaching settings, the SPED teacher was frequently in a subordinate position, which was considered to result from the lack of co-planning. The participants wished for more opportunities for collaboration, as it was considered beneficial for teachers and pupils. Time was considered as the most limiting factor of co-teaching and the amount of SPED resources was experienced as insufficient by the participants. These resources were also perceived as a limiting factor for the effective implementation of the three-step support model.